6(−8x+7)= 7(5x+6) Answer Attempt 3 out of 3 The equation
-
-
1 answer
-
18 views
-
-
1 answer
-
22 views
-
-
1 answer
-
asked by
Jett
-
57 views
-
6(−8x+7)=7(5x+6) Answer Attempt 3 out of 3 The equation has one solution and it is x, equalsx= .
-
1 answer
-
asked by
We Live We Love We LIE
-
38 views
-
−7(8x+5)=5x+10 Answer Attempt 3 out of 3 The equation has one solution and it is x, equalsx= .
-
1 answer
-
asked by
*+*Isabelle Hicks*+*
-
33 views
-
Complete the sentence based on the equation shown below.14, x, plus, 70, equals, h, of, 2, x, plus, 10 14x+70= h(2x+10) Answer
-
1 answer
-
9 views
-
Complete the sentence based on the equation shown below. h, of, minus, 3, x, plus, 6, equals, minus, 12, x, plus, 24 h(−3x+6)=
-
1 answer
-
9 views
-
-
1 answer
-
105 views
-
-
3 answers
-
16 views
-
-
1 answer
-
asked by
We Live We Love We LIE
-
81 views